FAKTOR-FAKTOR PEMILIHAN PEMASOK MATERIAL BANGUNAN - Fuk Jin Oei; Sudarno P Tampubolon; Dady Supriadi; Iwan B. Santoso (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2023)
Selection materials suppliers selectively are important things to be done by the contractor because it can save the cost of the project given the fact that more than half of project expenditure is for the material so we need the right management in the procurement of materials. In this study explains the factors to be considered contractor in choosing the material supplier. There are four main factors to be considered in the selection of contractors, namely material supplier quality, delivery, service, and cost which is then translated into 19 sub-variables. By using multiple linear regression obtained 3 factors that influence the decision of the contractor to buy material that is the amount of material being sent, delayed payment, and the accuracy of the information given price.